Does time matter? Intraspecific diversity of ribosomal RNA genes in lineages of the allopolyploid model grass Brachypodium hybridum with different evolutionary ages - Trunova, Dana; Borowska-Zuchowska, Natalia; Mykhailyk, Serhii; Xia, Kai; Zhu, Yuanbin; Sancho, Ruben; Rojek-Jelonek, Magdalena; Garcia, Sònia; Wang, Kai; Catalan, Pilar; Kovarik, Ales; Hasterok, Robert; et al. (BMC plant biology, 2024)
BACKGROUND: Polyploidisation often results in genome rearrangements that may involve changes in both the single-copy sequences and the repetitive genome fraction. In this study, we performed a comprehensive comparative analysis of repetitive DNA, with a particular focus on ribosomal DNA (rDNA), in Brachypodium hybridum (2n = 4x = 30, subgenome composition DDSS), an allotetraploid resulting from a natural cross between two diploid species that resemble the modern B. distachyon (2n = 10; DD) and B. stacei (2n = 20; SS). Taking advantage of the recurrent origin of B. hybridum, we investigated two genotypes, Bhyb26 and ABR113, differing markedly in their evolutionary age (1.4 and 0.14 Mya, respectively) and which resulted from opposite cross directions. To identify the origin of rDNA loci we employed cytogenetic and molecular methods (FISH, gCAPS and Southern hybridisation), phylogenetic and genomic approaches. RESULTS: Unlike the general maintenance of doubled gene dosage in B. hybridum, the rRNA genes showed a remarkable tendency towards diploidisation at both locus and unit levels. While the partial elimination of 35S rDNA units occurred in the younger ABR113 lineage, unidirectional elimination of the entire locus was observed in the older Bhyb26 lineage. Additionally, a novel 5S rDNA family was amplified in Bhyb26 replacing the parental units. The 35S and 5S rDNA units were preferentially eliminated from the S- and D-subgenome, respectively. Thus, in the more ancient B. hybridum lineage, Bhyb26, 5S and 35S rRNA genes are likely expressed from different subgenomes, highlighting the complexity of polyploid regulatory networks. CONCLUSION: Comparative analyses between two B. hybridum lineages of distinct evolutionary ages revealed that although the recent lineage ABR113 exhibited an additive pattern of rDNA loci distribution, the ancient lineage Bhyb26 demonstrated a pronounced tendency toward diploidisation manifested by the reduction in the number of both 35S and 5S loci. In conclusion, the age of the allopolyploid appears to be a decisive factor in rDNA turnover in B. hybridum.
Keywords: nrITS; rDNA loci; Genome, Plant; genom rostlinný; genetická variace; fylogeneze; Phylogeny; ribozomální DNA; molekulární evoluce; Evolution, Molecular; 5S rDNA NTS; RNA, Ribosomal; Brachypodium hybridum; geny rRNA; Genes, rRNA; RNA ribozomální; Brachypodium; Polyploidy; DNA, Ribosomal; Genetic Variation; 35S rDNA IGS, FISH; polyploidie